Remote Lesson Study as Continuing Professional Development for Physical Education Teachers - Colburn, Jeffrey; Knipe, Robert; Doherty, Brooke; Stephenson, Rachyl; Hamilton, Xiaofen (Journal of Teaching in Physical Education, 2026)
Purpose: This study investigated experiences of physical education teachers (PETs) participating in online remote andragogy-based lesson study (AbLS) during a pandemic. Method: Five PETs participated in this phenomenological case study. Seventeen online AbLS collaborative meetings took place via Zoom software. Three rounds of semistructured interviews were conducted and analyzed using collaborative qualitative analysis. Results: Three themes emerged: (a) AbLS facilitated depth of learning, increasing professional and individual growth; (b) AbLS structure influenced experience; and (c) the professional community of AbLS supported a natural adult learning (andragogical) environment. Discussion/Conclusion: Remote AbLS presented benefits for these PETs beyond professional learning that prior continuing professional development had not, including a sense of community, belonging, and professional worth. AbLS may have implications for research in perceived mattering and continuing professional development facilitation for PETs. Remote AbLS may bolster PETs in challenging local learning communities. © 2026 Human Kinetics, Inc.
Keywords: andragogy; dept.hms; marginalization; professional learning; remote communities